Priorities for Patient‐Centered Research in Valvular Heart Disease: A Report From the National Heart, Lung, and Blood Institute Working Group. Issue 9 (5th May 2020) - Lindman, Brian R.; Arnold, Suzanne V.; Bagur, Rodrigo; Clarke, Lindsay; Coylewright, Megan; Evans, Frank; Hung, Judy; Lauck, Sandra B.; Peschin, Susan; Sachdev, Vandana; Tate, Lisa M.; Wasfy, Jason H.; et al.
Abstract: Over the past decade, the field of valvular heart disease (VHD) has rapidly transformed, largely as a result of the development and improvement of less invasive transcatheter approaches to valve repair or replacement. This transformation has been supported by numerous well‐designed randomized trials, but they have centered almost entirely on devices and procedures. Outside this scope of focus, however, myriad aspects of therapy and management for patients with VHD have either no guidelines or recommendations based only on expert opinion and observational studies. Further, research in VHD has often failed to engage patients to inform study design and identify research questions of greatest importance and relevance from a patient perspective. Accordingly, the National Heart, Lung, and Blood Institute convened a Working Group on Patient‐Centered Research in Valvular Heart Disease, composed of clinician and research experts and patient advocacy experts to identify gaps and barriers to research in VHD and identify research priorities. While recognizing that important research remains to be done to test the safety and efficacy of devices and procedures to treat VHD, we intentionally focused less attention on these areas of research as they are more commonly pursued and supported by industry. Herein, we present the patient‐centered research gaps, barriers, and priorities in VHD and organized our report according to the "patient journey, " including access to care, screening and diagnosis, preprocedure therapy and management, decision making when a procedure is contemplated (clinician and patient perspectives), and postprocedure therapy and management. It is hoped that this report will foster collaboration among diverse stakeholders and highlight for funding bodies the pressing patient‐centered research gaps, opportunities, and priorities in VHD in order to produce impactful patient‐centered research that will inform and improve patient‐centered policy and care.